The Electrochemical Detection of Bisphenol A and Catechol in Red Wine - Chao Wang; Xiangchuan Wu; Xinhe Lin; Xueting Zhu; Wei Ma; Jian Chen (Foods)
The use of nanozymes for electrochemical detection in the food industry is an intriguing area of research. In this study, we synthesized a laccase mimicking the MnO2@CeO2 nanozyme using a simple hydrothermal method, which was characterized by modern analytical methods, such as transmission electron microscope (TEM), X-ray diffraction (XRD), and energy dispersive X-ray spectroscopy (EDX), etc. We found that the addition of MnO2 significantly increased the laccase-like activity by 300% compared to CeO2 nanorods. Due to the excellent laccase-like activity of the MnO2@CeO2 nanozyme, we developed an electrochemical sensor for the detection of hazardous phenolic compounds such as bisphenol A and catechol in red wines by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). We used the MnO2@CeO2 nanozyme to develop an electrochemical sensor for detecting harmful phenolic compounds like bisphenol A and catechol in red wine due to its excellent laccase-like activity. The MnO2@CeO2 nanorods could be dispersion-modified glassy carbon electrodes (GCEs) by polyethyleneimine (PEI) to achieve a rapid detection of bisphenol A and catechol, with limits of detection as low as 1.2 × 10−8 M and 7.3 × 10−8 M, respectively. This approach provides a new way to accurately determine phenolic compounds with high sensitivity, low cost, and stability.